PENINGKATAN KOMPETENSI KEPALA RAUDHATUL ATHFAL (RA) DALAM MENGEMBANGKAN PEMBELAJARAN MELALUI MATA DIKLAT PENGEMBANGAN KOMPETENSI SUPERVISI - Yayah Kusbudiyah (Tatar Pasundan : Jurnal Diklat Keagamaan, 2018)
Head of Raudhatul Athfal (RA) who is a teacher who is given additional task as Head of school, is required to have supervision competence as a provision to give lesson to children and guidance to RA teacher. Based on data on educational background of Head of RA, only a small part of Head who have background of Early Childhood Education. This is the biggest obstacle for the Head of RA in teaching. The discussion of this paper is limited to Academic supervision, more specifically discussing about learning and learning at Raudhatul Athfal. The Theory Framework is a discussion of Core Competencies, Basic Competencies contained in Curriculum 2013 for RA. The results of research in the form of findings that the head of RA still have a lot to learn about the strategy of learning, especially the strategy through the game in accordance with the field of development that became the learning objectives in RA as contained in indicators of learning that can be observed through Permendikbud no 137 and 146 in2014 about Curriculum 2013 for early childhood and Decree of the Director General of Education no 3489 in 2016. The author recommends for the type of training, should be given material more practical and applicable material. It is expected that this kind of training can be done with more frequencies.  Key words: Competence, supervision, the head of RA.